THE PROBLEM OF PETTY-THEFTS TO BIG CORPORATIONS: A JURISPRUDENTIAL ANALYSIS - Cordero Campos, Farid (2020)
This article analyzes the jurisprudence of the Third Chamber of the Supreme Court of Justice of Costa Rica, regarding the judicialization of theft of assets of small value, in which the injured party is made up of companies of great economic power, from the perspective postpositivist. This analysis is based on the approach to judicial argumentation, in which the object of study is based on the most important sentences issued by the highest criminal court in Costa Rica in the matter